2022
DOI: 10.7759/cureus.29224
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Complications as Risk Factors for Postpartum Psychosis: A Systemic Review

Abstract: The aim of this research paper is to conduct a systematic review of periparturient complications as risk factors of postpartum psychosis. The investigation of risk factors for maternal psychosis following childbirth is complicated by the risk of confounding by a previous psychiatric history; therefore, this systematic review focuses on labor complications as risk factors among women without any previous psychiatric hospitalizations or diagnoses.Articles were collected and analyzed from the PubMed, MEDLINE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…These were included to be as broad as possible in our search. Our findings are similar to a previous systematic review of peripartum complications in relation to postpartum psychosis ( 23 ), which showed a lack of replication for any single risk factor. Notably this previous systematic review had limited information on included studies, did not formally assess study quality, and included study designs with high risk of bias, such as case reports.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These were included to be as broad as possible in our search. Our findings are similar to a previous systematic review of peripartum complications in relation to postpartum psychosis ( 23 ), which showed a lack of replication for any single risk factor. Notably this previous systematic review had limited information on included studies, did not formally assess study quality, and included study designs with high risk of bias, such as case reports.…”
Section: Discussionsupporting
confidence: 83%
“…The following databases were searched from inception until June 2021: MEDLINE, EMBASE, PsychInfo. References from a recent review ( 23 ) examining associations between obstetric complications and postpartum psychosis were searched. Titles, abstracts, and keywords were searched using the combinations of terms shown below, with the full search strategy outlined in the Supplementary Materials:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We think that boosting the immunity of mothers, which can lead to less severe forms and reduce the workload and the feeling of work exhaustion. Furthermore, in the postpartum period, several cases of puerperal psychosis were observed during the COVID-19 pandemic, which seems to be related to maternal anxiety about themselves and their newborns and being obsessed by possible perinatal complications [36,37]. So, the mothers' awareness of the degree of protection when vaccinated with a booster dose may help.…”
Section: F O R P U B L I C a T I O N 10mentioning
confidence: 99%
“…Risk factors for PP include preeclampsia, eclampsia, peripartum infections, cesarean section, and a personal or family history of bipolar disorder [ 12 , 13 ]. Although rare in the general population, PP is significantly more common among women with a personal history of bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%